Perioperative Management of Neuroanesthesia in Patients with Supratentorial Tumors Who Have Excised Tumors Using Neuroprotection Technique and Total Intravenous Anesthesia - Aditiarso, Candra; Laksono, Buyung Hartiyo (Journal of Anaesthesia and Pain, 2024)
Background: Neuroanesthesia management presents a unique challenge for anesthesiologists. They must provide an optimal surgical condition without worsening the patient's neurological deficits. Therefore, we need drugs with neuroprotective abilities. This case report explains the perioperative management of neuroanesthesia in patients with supratentorial tumors who have excised tumors using a neuroprotection technique and total intravenous anesthesia (TIVA).Case: A 43-year-old female patient with space-occupying process cerebri with the differential diagnosis of meningioma frontotemporal dextra, post trepanation frontal sinistra tumor excision, edema cerebri, and hydrocephalus on ventriculoperitoneal shunt. On physical examination, Glasgow coma scale E3M6Vaphasia, aphasia and left hemiparesis were found. She underwent a tumor excision procedure with total intravenous anesthesia modified with neuroprotection techniques and total intravenous anesthesia techniques using 300 mg thiopental, 2 mg midazolam, 150 µg fentanyl, 80 mg lidocaine, and 50 mg rocuronium. Intraoperative anesthesia management was carried out by administering propofol 50 mg/hour, fentanyl 50 µg/hour, and atracurium 15 mg/hour.Conclusion: Total intravenous anesthesia is a complete general anesthesia method used in all intravenous agents, where the benefits of this method are used in neurosurgery, including accelerating the patient's return from the effects of anesthesia, faster recovery of cognitive function, as well as reducing intracranial pressure and the risk of ischemia.